2022
DOI: 10.1136/rmdopen-2021-001712
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of electronic drug monitoring feedback to increase adherence in patients with RA initiating a biological DMARD: a randomised clinical trial

Abstract: ObjectiveMedication non-adherence in rheumatoid arthritis (RA) is associated with disease flares, increased disability and increased costs. This study assessed the effectiveness of electronic monitoring feedback (EMF) on medication adherence in patients with RA starting with or switching to a new biological disease-modifying antirheumatic drug (bDMARD).MethodsIn this randomised controlled trial, bDMARD starters were assigned to the intervention or control group and followed for 1 year. The intervention group r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Also, unclear reporting of time points due to multiple anomalies). Hebing et al 52 2022, RA To assess effectiveness of electronic monitoring feedback ( EMF) on medication adherence in patients with RA starting with or switching to new biological disease modifying antirheumatic drugs ( bDMARDs). None stated Participants assigned to group and monitored for 12 months.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, unclear reporting of time points due to multiple anomalies). Hebing et al 52 2022, RA To assess effectiveness of electronic monitoring feedback ( EMF) on medication adherence in patients with RA starting with or switching to new biological disease modifying antirheumatic drugs ( bDMARDs). None stated Participants assigned to group and monitored for 12 months.…”
Section: Resultsmentioning
confidence: 99%
“…Post-intervention data [6 week] used instead) . -Baseline, 6 weeks (immediate post-intervention) and 12 weeks Medium 9) Hebing et al 52 2022; Netherlands Randomised: 206 Intervention 104 Control 102 Intervention 53.5 (±12.1) Contro l 51.2 (±13.6) Overall 52.4 ( not stated ) Intervention Male 31 (30%) Female 73 (70%) Control Male 28 (27%) Female 74 (73%) Overall Male 59 (28.6%) Female 147 (71.4%) RA Outpatient clinic RCT; unblinded -Completion: no 1° completion data (ITT used) -Baseline and every 3 months (12 months duration) High 10) Keefer at al 53 2012; USA Randomised: 30 Intervention 17 (16 1° Endpoint analysis) Control 13 (12 1° Endpoint analysis) Intervention 34.5 (29–39) Control 40.8 (31–49) (No SD stated, only range) Overall 37.7 (not stated) Overall Male 10 (30%) Female 18 (70%) (Not stated/arm, but overall values given). IBD Outpatient clinic Pilot RCT; unblinded -Completion: 28 (93.3%) (analysis type not stated) -Baseline and 8 weeks Medium 11) Landtblom et al 36 2019; Sweden Randomised: 93 Intervention 46 Control 47 Intervention 41 (±13.2) Control 38 (±10.9) Overall 39.5 (not stated) Intervention Male 14 (37%), Female 24 (63%) Control Male 15 (38%) Female 24 (62%) Overall Male 29 (31.2%) Female 48 (51.6%) MS Outpatient (multicentre) RCT; single-blinded (participants) -Completion: 53 (57%) (ITT and per protocol used) -Baseline, 6 and 12 months High …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 100 , 101 Some studies have already shown that telemedical appointments may replace certain types of physical visits (e.g. follow-up visits) leading to non-inferior outcomes 102 104 Ideally future hybrid management of care can be prepared with patients beforehand, using examples like guides for musculoskeletal examination for telemedicine. 105 All these advancements might need standard frameworks and regulations as well as manuals for rheumatology practitioners to act in a legal, best-practice, and financially reimbursed space.…”
Section: Introductionmentioning
confidence: 99%
“…1 They are also an important source of treatment nonadherence, with deleterious effects on disease outcomes. 2,3 Gaining insight into patients' experiences with medication side effects could help inform the development of new shared decision-making approaches to enhance treatment adherence and long-term disease and health outcomes.…”
mentioning
confidence: 99%